LRF inhibits p53 expression in colon cancer cells via modulating DAP5 activity. (28th August 2017) - Zhu, Min; Wang, Peng; Feng, Fan; Li, Ming‐Yang
Abstract : The p53 protein plays a critical role in suppression of tumour growth; its regulation is not fully understood. Leukaemia/lymphoma‐related factor (LRF) promotes tumour cell growth. This study tests a hypothesis that LRF inhibits p53 expression in colon cancer cells. In this study, human colon cancer cell lines, LIM1215 and HCT116 cells, were used. The expression of LRF and p53 in the cells was analysed by quantitative reverse transcription polymerase chain reaction and Western blotting. We observed that the expression of protease‐activated receptor 2 (PAR2) was detected in both LIM1215 and HCT116 human colon cancer cells. Activation of PAR2 increased the expression of LRF and inhibited the p53 expression in the cancer cells. We also detected a complex of LRF and DAP5, one of the p53 gene transcription factors. The interaction of LRF and DAP5 resulted in the repression of p53 expression in the colon cancer cells. In conclusion, PAR2 activation increases the expression of LRF in colon cancer cells, which interacts with DAP5 to repress the p53 expression. Leukaemia/lymphoma‐related factor may be a novel target in the treatment of colon cancer.